2021
DOI: 10.1186/s13012-021-01087-2
|View full text |Cite
|
Sign up to set email alerts
|

A myriad of factors influencing the implementation of transitional care innovations: a scoping review

Abstract: Background Care transitions of older persons between multiple care settings are frequently hampered by various issues such as discontinuous care delivery or poor information transfer among healthcare providers. Therefore, several innovations have been developed to optimize transitional care (TC). This review aims to identify which factors influence the implementation of TC innovations. Methods As part of TRANS-SENIOR, an international innovative tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 65 publications
1
36
0
Order By: Relevance
“…This is also true for changing health personnel's practice related to patient's minor children (11,17). Implementation science focuses on studying methods for promoting the uptake of consolidated research findings into routine healthcare practice and health policy, and many researchers have studied which factors have an impact on the implementation of new practices (16,18,19). A recent scoping review conducted by Fakha et al (18), identified an interplay of 25 main factors that acted as barriers and facilitators during the implementation of diverse health care innovations (18).…”
Section: Implementation Of Practice Changesmentioning
confidence: 99%
See 2 more Smart Citations
“…This is also true for changing health personnel's practice related to patient's minor children (11,17). Implementation science focuses on studying methods for promoting the uptake of consolidated research findings into routine healthcare practice and health policy, and many researchers have studied which factors have an impact on the implementation of new practices (16,18,19). A recent scoping review conducted by Fakha et al (18), identified an interplay of 25 main factors that acted as barriers and facilitators during the implementation of diverse health care innovations (18).…”
Section: Implementation Of Practice Changesmentioning
confidence: 99%
“…Implementation science focuses on studying methods for promoting the uptake of consolidated research findings into routine healthcare practice and health policy, and many researchers have studied which factors have an impact on the implementation of new practices (16,18,19). A recent scoping review conducted by Fakha et al (18), identified an interplay of 25 main factors that acted as barriers and facilitators during the implementation of diverse health care innovations (18). There is a wide range of interrelated factors existing at multiple levels that determine the success of the implementation of innovations (18), which explains why changing clinical practice is challenging, time consuming and needs to be monitored over time.…”
Section: Implementation Of Practice Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…Even with appropriate program offering to patients and available reimbursement with recent increased national trends of utilization, 27 the acceptance of transitional care programs may vary 24 , 28 , 29 and addressing both medical and social needs 30 after discharge will be required to have impact on longer-term outcomes. Future work will require focus not only on utilizing the risk score to inform resource allocation for post-discharge initiatives and subsequent assessment of clinical outcomes but on implementation strategies to improve uptake of the programs offered.…”
Section: Discussionmentioning
confidence: 99%
“…Participating NHs did commonly mentioned leadership support as an important factor for facilitating implementation. Several studies have identified leadership support and organizational culture as important factors in improving NH care 27–35 . Measures of leadership support in future studies could include providing dedicated time for champions, leadership turnover, execution of a participation agreement at the beginning of the project by facility and corporate leaders, and utilizing regional nurses for monitoring intervention implementation.…”
Section: Discussionmentioning
confidence: 99%